2012
DOI: 10.1590/s0100-736x2012001200002
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fenotípica, produção de biofilme e resistência aos antimicrobianos em isolados de Staphylococcus spp. obtidos de casos de mastite em bovinos e bubalinos

Abstract: No presente estudo, objetivou-se avaliar a sussuscetibilidade aos principais antimicrobianos e realizar uma caracterização fenotípica e genotípica de isolados de Staphylococcus spp. obtidos de casos de mastite em vacas (n=30) e búfalas (n=30). A suscetibilidade foi avaliada pela técnica de disco-difusão e a presença de bomba de efluxo foi avaliada utilizando-se Ágar Mueller Hinton (MH) adicionado de brometo de etídeo e pesquisa do gene msrA. Pela técnica da Reação em Cadeia da Polimerase (PCR) ainda foram iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(28 reference statements)
1
2
1
4
Order By: Relevance
“…Of the 15 isolates, 40% were classified as strongly adherent, i.e., strongly biofilm forming. GUIMARÃES et al (2012), when studying the production of biofilm by Staphylococcus, obtained different results from those observed in our study, because 13/30 (43.3%) of the strains analyzed did not form biofilms and only 8/30 (26.7%) were strongly biofilm formers. OLIVEIRA et al (2006), working with mastitis isolates, found 18.7% of the S. aureus strains producing biofilms, while NOEL et al (2016), who studied a biofilm formation in Staphylococcus spp.…”
Section: Resultscontrasting
confidence: 99%
“…Of the 15 isolates, 40% were classified as strongly adherent, i.e., strongly biofilm forming. GUIMARÃES et al (2012), when studying the production of biofilm by Staphylococcus, obtained different results from those observed in our study, because 13/30 (43.3%) of the strains analyzed did not form biofilms and only 8/30 (26.7%) were strongly biofilm formers. OLIVEIRA et al (2006), working with mastitis isolates, found 18.7% of the S. aureus strains producing biofilms, while NOEL et al (2016), who studied a biofilm formation in Staphylococcus spp.…”
Section: Resultscontrasting
confidence: 99%
“…Already in the Federal District (Brasília) evaluated 60 samples of Staphylococcus spp. in clinical cases and sub-clinical cases of bovine and bubaline mastitis and found the mecA gene in one (3.30%) of the bubaline samples and three (10%) of the bovine samples [21]. The absence of the mecA gene in the present study may be associated with the development of resistant bacteria through another mechanism, such as the overproduction of beta-lactamases [19].…”
Section: Discussionsupporting
confidence: 43%
“…Taking this into consideration, the present paper where all the Staphylococcus aureus were negative for mecA, only the samples Re 82, Re 62 and Re 40 can be considered resistant to oxacillin. Results of the present study can be confronted with others authors that identify this gen in 11% of the milk samples from refrigeration tank in Minas Gerais (DIAS et al, 2011) and 6,7% in milk samples of cows with subclinical and clinical mastitis from the Distrito Federal (GUIMARÃES et al, 2012). A study performed with 272 milk samples from cows positive to the California Mastitis Test from properties of the south Fluminense region didn't detected the mecA gen, in other words, the results are similar to the ones found in this work (MENDONÇA et al, 2012).…”
Section: Resultsmentioning
confidence: 62%